(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2023)
The prevention of damage resulting from head injuries is a topic of great interest for the scientific community, due to the social consequences arising from the high mortality and disability rates associated with these events. In particular, research focuses on the study of the biomechanical pathways that lead to the development of the various types of brain injury that occur as a result of impacts. In this context, instrumented devices capable of acquiring data during the collision, such as the skull and brain kinematic physical quantities and the stress development inside the brain tissue, will prove to be very helpful; these data can subsequently be analysed and used for numerical simulations with techniques such as finite element analysis. On this subject, the use of advanced technologies for the production of the components of a physical headform, including also a biofidelic skull and a brain simulant, can play an outstanding role, allowing the creation of replicas of the human head characterised by a high level of biofidelity. This feature will be very important for the development of protective devices, such as helmets. The present work describes the development of a physical head prototype, highlighting the importance of the choice of materials and identifying the aspects where the use of advanced additive manufacturing technologies may be expected to provide an effective contribution. Experimental activities on an Instrumented Human Head Surrogate (IHHS) implemented at the University of Padova confirmed the importance of this subject, giving interesting suggestions for future developments. The porous structure of the trabecular bone could be reproduced using additive manufacturing technologies and the brain simulant biofidelity could be improved by means of new materials like gelatines and new elements simulating bridging veins. Acknowledgments Research funding: The research has received funding from the project SAFE (Smart creAtivity for saFety and rEstart). Author’s statement The authors state no conflict of interest. Informed consent has been obtained from all individuals included in this study.